Evaluation of Frequency of Microbial Contamination in Clinical Setting Surface in Dental School of Mashhad University of Medical Sciences - Fatemeh Khorakian; Taraneh Movahed; Kiarash Ghazvini; Seddighe Karbasi; Salahodin Tabrizi Nouri; Lida Bahramian; Mohamad Taghi Shakeri (Mashhad University of Medical Sciences, 2017)
Introduction: Surfaces mostly touched during dental treatments can be areservoir for infections and lead to cross-infection. The aim of the presentstudy was to evaluate the incidence of microbial infection of clinical surfaces in Mashhad Faculty of Dentistry. Materials and Methods: Surface samples were randomly collected from unit headrest, light handle, and tabure of 10% of active dental units in Mashhad Dental Faculty. Samples were collected at two time points including beginning of the day and midday after surface disinfection. Samples were collected and transferred to the microbiology laboratory to determine the number of various microorganisms including staphylococcus, streptococcus, micrococcus, bacillus, tetragen, corena, and yeast. Data was analyzed by using Kruskal-Wallis test. P-value less than 0.05 were considered significant. Results: The highest rate of contamination of headrest was observed at Prosthodontics Department, and the highest rate of contamination of light handle respectively in Endodontics, Pediatrics, and Prosthodontics departments. Furthermore, Prosthodontics Department showed the highest rate of tabure contamination. Kruskal-Wallis test revealed no significant difference in total microorganisms at different departments in various surfaces. A significant difference was found between departments regarding micrococcus infection (P